Теоретичні дослідження впливу зміни тиску в електропневматичному гальмівному приводі на динаміку руху коліс КТЗ - Дон, Євген Юрійович (НТУ "ХПІ", 2017)
В роботі проаналізовано та узагальнено результати дослідження впливу темпу зміни тиску в електропневматичному гальмівному приводі на процес гальмування автомобільного колеса. Описано вплив принципів керування на динаміку руху колісного транспортного засобу та визначено спосіб зміни темпу наповнення гальмівної камери під час моделювання робочих процесів електропневматичного гальмівного приводу транспортного засобу.

The paper analyzed and summarized the results of studies of the effect of the rate of change of pressure in electropneumatic brake actuator for a braking process of a vehicle wheel. Describes the impact of management principles on the dynamics of the wheeled vehicle and the determined way to change the rate of filling of the brake chamber during simulation of work processes of an electropneumatic brake of the vehicle. The aim of this work is the theoretical analysis of the influence of the nature of pressure changes in the brake actuator on the choice of control principle electropneumatically modulators pressure. To ensure rolling wheels with rational slippage rate of filling of the brake chamber, after reaching 10% slip, you should reduce to not less than 60%.
Theoretical studies of the effect of the rate of change of pressure in the brake actuator elektropneumatische on the dynamics of the wheels of the wheeled vehicle
Keywords: електропневматичне гальмівне керування; гальмівна система; ПГП; колісний транспортний засіб; КТЗ; actuator; brake system; EBS